The designer's guide to the Cortex-M processor family a tutorial approach - Martin, Trevor (Newnes, 2013)
The Designer's Guide to the Cortex-M Microcontrollers gives you an easy-to-understand introduction to the concepts required to develop programs in C with a Cortex-M based microcontroller. The book begins with an overview of the Cortex-M family, giving architectural descriptions supported with practical examples, enabling you to easily develop basic C programs to run on the Cortex-M0/M0+/M3 and M4 and M7. It then examines the more advanced features of the Cortex architecture such as memory protection, operating modes, and dual stack operation. Once a firm grounding in the Cortex-M processor has been established the book introduces the use of a small footprint RTOS and the CMSIS-DSP library. The book also examines techniques for software testing and code reuse specific to Cortex-M microcontrollers. With this book you will learn: the key differences between the Cortex-M0/M0+/M3 and M4 and M7; how to write C programs to run on Cortex-M based processors; how to make the best use of the CoreSight debug system; the Cortex-M operating modes and memory protection; advanced software techniques that can be used on Cortex-M microcontrollers; how to use a Real Time Operating System with Cortex-M devices; how to optimize DSP code for the Cortex-M4; and how to build real time DSP systems.
Online resource; title from PDF title page (Safari, viewed June 11, 2013)
Keywords: RISC microprocessors; Microprocessors; RISC (Microprocesseurs)